MECHANISMS FOR INCREASING THE INNOVATIVE ACTIVITY OF FOOD INDUSTRY ENTERPRISES BASED ON DIGITAL TECHNOLOGIES - Abdunabiyev , Sirojiddin (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
The article analyzes the mechanisms for increasing the innovative activity of food industry enterprises based on digital technologies. The study examines the impact of ERP systems, automated production, digital logistics, electronic document management, artificial intelligence, and data analytics on innovative product development, production efficiency, and competitiveness. The findings show that digital technologies are an important factor in accelerating innovation processes, reducing costs, and improving product quality in food industry enterprises.